A new subgenus Wraseiellus of the genus Pterostichus Bonelli (Coleoptera, Carabidae, Pterostichini) and new species descriptions - Shi, Hongliang; Sciaky, Riccardo; Liang, Hongbin; Zhou, Hongzhang (Zootaxa, 2013)
A new subgenus Wraseiellus new subgenus (type species: Pterostichus andrewesi Jedlička 1931) of the genus Pterosti-chus from China is described. Eight species and one subspecies are recognized in the new subgenus including three new species and one new subspecies: Pt. (Wraseiellus) comatus new species (Guangxi: Maoershan, N25.87º, E110.42º), Pt. (Wraseiellus) crassiapex new species (Hubei: Tiechanghuang, N30.75º, E110.30º), Pt. (Wraseiellus) pseduodiversus new species (Yunnan: Luguhu, N27.63º, E100.82º), Pt. (Wraseiellus) stictopleurus cangshanensis new subspecies (Yunnan: Cangshan, N25.63º, E100.14º). Feronia crebrepunctata Straneo, 1937 is newly proposed as junior synonym of Pterosti-chus meyeri Jedlička, 1934. A key to all known species and subspecies, images of habitus and genitalia, and distribution maps are provided.